Allergies and COVID‐19 vaccines: An ENDA/EAACI Position paper. Issue 8 (5th March 2022) - Barbaud, Annick; Garvey, Lene Heise; Arcolaci, Alessandra; Brockow, Knut; Mori, Francesca; Mayorga, Cristobalina; Bonadonna, Patrizia; Atanaskovic‐Markovic, Marina; Moral, Luis; Zanoni, Giovanna; Pagani, Mauro; Soria, Angèle; et al.
Abstract: Background: Anaphylaxis, which is rare, has been reported after COVID‐19 vaccination, but its management is not standardized. Method: Members of the European Network for Drug Allergy and the European Academy of Allergy and Clinical Immunology interested in drug allergy participated in an online questionnaire on pre‐vaccination screening and management of allergic reactions to COVID‐19 vaccines, and literature was analysed. Results: No death due to anaphylaxis to COVID‐19 vaccines has been confirmed in scientific literature. Potential allergens, polyethylene glycol (PEG), polysorbate and tromethamine are excipients. The authors propose allergy evaluation of persons with the following histories: 1—anaphylaxis to injectable drug or vaccine containing PEG or derivatives; 2—anaphylaxis to oral/topical PEG containing products; 3—recurrent anaphylaxis of unknown cause; 4—suspected or confirmed allergy to any mRNA vaccine; and 5—confirmed allergy to PEG or derivatives. We recommend a prick‐to‐prick skin test with the left‐over solution in the suspected vaccine vial to avoid waste. Prick test panel should include PEG 4000 or 3500, PEG 2000 and polysorbate 80. The value of in vitro test is arguable. Conclusions: These recommendations will lead to a better knowledge of the management and mechanisms involved in anaphylaxis to COVID‐19 vaccines and enable more people with history of allergy to be vaccinated. Abstract :